Almanach Demi Stock 1986-2 : Espaces de notre temps. (Paris : Galerie 1900-2000, 1986)
Léger, Fernand ; Breuer, Leo ; Ferren, John ; Servranckx, Victor ; Brauner, Victor ; Dax, Adrien ; Ernst, Max ; Franès, Esteban ; Hérold, Jacques ; Höch, Hannah ; Jean, Marcel ; Polinier, Pierre ; Oelze, Richard ; etc.
Almanach Demi Stock 1986-2 : Espaces de notre temps, Galerie 1900-2000, Paris, 25.10 - 02.11.1986
boek